Um panorama de pesquisas sobre o ensino e a aprendizagem do cálculo diferencial e integral: 2003 a 2013 - Marini, Wagner (2015)
The objective of this dissertation is to carry out a study focused on the research of Teaching and Learning of Calculus in Exact initial courses, produced in Brazil from 2003 to 2013. This study involves survey, categorization, and synthesis of the results and it was organized through a Panorama that includes dissertations, theses and articles focused on this theme. Methodological procedures that lead to the analysis of the collected material are those appropriate to qualitative research theorist related to state of the art. The analysis of the work constituents of Panorama aimed to highlight the relationship between the theories of sustaining, methodologies adopted and philosophical conceptions with the approach and development of work itself, having as reference, especially what is indicated by the English (2010). Furthermore, the analysis guided by the quest to answer the four questions drawn up for this purpose, has allowed the observation that there is a diversity of theories used as support of the work and a profusion of outcomes that allow the desirable bridge between the theory and the practice of Teaching and Learning the Differential and Integral Calculus. Results are highlighted based on the need of the area to establish consensus